The interplay of retirement policy and externalisation strategies towards older workers in Polish and German enterprises - Paula Aleksandrowicz (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2006)
Throughout the last decades, employment rates of older workers in most European countries have been falling, as has the age of exit from the labour force. This development does not only exert heavy financial pressures on social security systems but inhibits also the potential of older workers to shape their lives actively. The reasons for that trend can be found at three dimensions: the early retirement options inherent in the public retirement system, the internalisation and externalisation strategies of enterprises, and the retirement preferences of individual workers. The paper will present recent empirical data on the way enterprises utilise early retirement options created by the public retirement system for externalising older workforce. The data was collected in expert interviews with personnel managers and works council members in Polish and German enterprises. Many of the studied companies are undergoing restructuring and are cutting employment levels. This clearly dominates their personnel policy towards older workforce. Therefore, externalisation strategies outbalance any possible tendencies to integrate older workers, like considering them to a greater extent in recruitment. The paper will also discuss the possible future development of externalisation strategies in the light of pension reforms carried out in Germany and Poland.
Keywords: 320